Behind the Concept of 'Zero Carbon Emissions' In Indonesia: a Symbolic Construction Analysis - Karen Kusnadi; Siti Nur Ayu (Riviera Publishing, 2023)
As one of the world's largest contributors to greenhouse gas emissions, Indonesia has set a target for zero carbon emissions by 2060. However, these targets and the derived efforts have not been accompanied by adequate understanding among the Indonesian populace. This research aims to comprehend and analyze the concept of zero carbon emissions in Indonesia. Employing a qualitative approach with content analysis methodology, the study discovered that one of the causes for this lack of understanding is the ineffective messaging concerning 'zero carbon emissions' in Indonesia. The symbolic constructs created do not align with the intended messages, in line with the recommendations for effective environmental communication concepts, encompassing aspects such as message types, functions, word choices, genres, relevance, and consistency. This research implies an enhancement in public awareness regarding the concept of zero carbon emissions in Indonesia. The outcomes of this study can also provide insights to the government and environmental organizations to formulate more effective policies in communicating the message of 'zero carbon emissions.' By implementing these recommendations, environmental communication regarding the concept of zero carbon emissions in Indonesia can become more effective, motivating individuals to actively participate in efforts to reduce carbon emissions.